1956
DOI: 10.1063/1.1743019
|View full text |Cite
|
Sign up to set email alerts
|

Electron Attachment in Sulfur Hexafluoride Using Monoenergetic Electrons

Abstract: Electron attachment leading to the formation of SF6— and SF5— in sulfur hexafluoride has been investigated using nearly-monoenergetic electrons of established energies of less than 2 ev. The dissociative attachment process leading to the formation of SF5— maximizes at less than 0.1 ev and then decreases to zero at approximately 1.5 ev. In the case of resonance capture leading to the formation of SF6—, the capture process occurs at less than 0.1 ev and only over an energy range estimated to be not larger than 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

1967
1967
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(21 citation statements)
references
References 7 publications
2
18
0
1
Order By: Relevance
“…The ratio of SF^"/SF^" was less than 1/20, which is in agreement with Hickam and Fox [21] , and it is tempting to explain the ineffectiveness of SF, as an inhibitor by the fact that too few residual radicals are formed. However, this may not be a valid explanation, since Hickam and Berg [22] found that the ratio of SF,-"/SF^" depends on temperature, being .25 at 80°C and 1.5 at 280^C .…”
Section: Proposed Inhibition Mechanismsupporting
confidence: 66%
“…The ratio of SF^"/SF^" was less than 1/20, which is in agreement with Hickam and Fox [21] , and it is tempting to explain the ineffectiveness of SF, as an inhibitor by the fact that too few residual radicals are formed. However, this may not be a valid explanation, since Hickam and Berg [22] found that the ratio of SF,-"/SF^" depends on temperature, being .25 at 80°C and 1.5 at 280^C .…”
Section: Proposed Inhibition Mechanismsupporting
confidence: 66%
“…The estimated result shows that electron energy in the reactor is more than 0.3 eV. Hickam and Fox (1956) have reported the variation in the electron energy of the yield of SF; and SF; by electron impact in SF,, and shown that SF; is the main ion in case that electron energy is more than 0.3 eV. It can thus be seen that the dissociative attachment given by Eq.…”
Section: Electron Attachment To Sfmentioning
confidence: 77%
“…1 and 2 (Hickam and Fox, 1956). Reaction-rate constants of electron attachment depend on electron energy, and electron energy depends on the ratio of electric field strength, E , to pressure, p , or, E/p.…”
Section: Electron Attachment To Sfmentioning
confidence: 94%
See 1 more Smart Citation
“…·ÑÓÑÛÑ ËÊÄÇÔÕÐÑ ÒÓËÏÇÐÇÐËÇ ÅÇÍÔÂ×ÕÑÓËAE ÔÇÓÞ, ÑÃÓÂÊÖáÜÇÅÑ AEÑÎÅÑÉËÄÖÜËÇ ËÑÐÞ, Ä ÍÂÚÇÔÕÄÇ ÅÂÊÑÄÑÅÑ ËÊÑÎâÕÑÓ AEÎâ ÒÓÇAEÑÕÄÓÂÜÇÐËâ àÎÇÍÕÓËÚÇÔÍÑÅÑ ÓÂÊÓâAEÂ Ä ÄÞÔÑÍÑÄÑÎßÕ-ÐÞØ ÖÔÕÓÑÌÔÕÄÂØ Ë ÅÇÐÇÓÂÕÑÓÂØ [35].¯ÇAEÂÄÐÑ ÃÞΠÑÕ-ÏÇÚÇРÄÑÊÏÑÉÐÂâ ÓÑÎß ÔÒËÐÑÄÞØ ÊÂÒÓÇÕÑÄ ÍÄÂÓÕÇÕÐÞØ ÔÑÔÕÑâÐËÌ°ª Ä ÄÑÊÐËÍÐÑÄÇÐËË à××ÇÍÕ ÑÕÓËÙÂÕÇÎßÐÑÅÑ AEË××ÇÓÇÐÙËÂÎßÐÑÅÑ ÔÑÒÓÑÕËÄÎÇÐËâ Ä ÏËÍÓÑàÎÇÍÕÓÑÐ-ÐÞØ ÖÔÕÓÑÌÔÕÄÂØ [30].…”
Section: £äçAeçðëç°õunclassified